2020
DOI: 10.1038/s41416-020-01184-x
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating T-cell markers in cervical carcinogenesis: a systematic review and meta-analysis

Abstract: Background The host adaptive immune response helps determine which cervical HPV infections persist and progress to precancer and cancer, and systematic characterisation of T-cell infiltration would help inform key steps in cervical carcinogenesis. Methods A systematic review and meta-analysis were conducted of infiltrating T-cells in normal cervix, low-grade lesions, high-grade lesions, and invasive cancers including epithelial, stromal, and total tissue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 107 publications
1
60
1
Order By: Relevance
“…T cells showed the decreasing trend from normalcy and LSIL to HSIL with higher infiltration in normalcy, while bioinformatically T cell infiltrated lowest in cancer contradictive with experimental results ( Figure 2B and CD8 + T cells infiltrated higher in normalcy and cancer, lower in LSIL and HSIL stages ( Figure 2D). 26 The infiltration number of regulatory T cells (Tregs), GZMB + cytotoxic T cells increased from normalcy to HSIL and fell from HSIL to cancer ( Figure 2D). Of note, neutrophils and NK cells significantly higher than other stages ( Figure 2C), which was the opposite to bioinformatical result showing the neutrophils was the significantly lowest in cancer ( Figure 2B).…”
Section: Changes Of Local Immune Cells and Immune-modulatory Genes mentioning
confidence: 99%
“…T cells showed the decreasing trend from normalcy and LSIL to HSIL with higher infiltration in normalcy, while bioinformatically T cell infiltrated lowest in cancer contradictive with experimental results ( Figure 2B and CD8 + T cells infiltrated higher in normalcy and cancer, lower in LSIL and HSIL stages ( Figure 2D). 26 The infiltration number of regulatory T cells (Tregs), GZMB + cytotoxic T cells increased from normalcy to HSIL and fell from HSIL to cancer ( Figure 2D). Of note, neutrophils and NK cells significantly higher than other stages ( Figure 2C), which was the opposite to bioinformatical result showing the neutrophils was the significantly lowest in cancer ( Figure 2B).…”
Section: Changes Of Local Immune Cells and Immune-modulatory Genes mentioning
confidence: 99%
“…The current understanding is that Th2 polarization of immune responses in the HPV infected lesions leads to blunting of CTL responses and immune evasion which aids the virus to persist. A systematic review and meta-analysis have recently been published on the distribution of T cell infiltrates across cervical disease states (reviewed in Litwin et al, 2020). In brief, increased T cell infiltrates have been reported in normal cervices and CxCa tissues, whereas relatively lower numbers of CD3+, CD4+, and CD8+ cells were seen in all three types of CINs.…”
Section: Effector Immune Infiltrates and Inflammation In Cervical Carcinogenesismentioning
confidence: 99%
“…The statistics for 2018 indicated that 570,000 new cases were recorded with nearly 311,000 deaths, majorly in low and middle-income countries (Bray et al, 2018). While screening has greatly impacted the incidence of CxCa in high-income countries, which would further get reduced with prophylactic vaccination programs, the global incidence of this cancer, however, will not change much for the next 20 years, due to inconsistencies in both screening and vaccination programs throughout the world (reviewed in Litwin et al, 2020). Human papilloma virus (HPV) infections are one of the most common sexually transmitted infections.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, local increases in natural regulatory T cells (nTreg cells) which express the transcription factor forkhead box P3 (FOXP3) and IL-2 receptor (CD25), 20 has been associated with subcutaneous immunotherapy, because patients after immunotherapy have increased numbers of CD4 + CD25 + cells. 21 , 22 , 23 It has been shown that FoxP3+CD25 + regulatory T-cell infiltration is high in persistent and precancerous lesions, and longitudinal data show improved outcomes with lower regulatory T-cell levels, 24 which could exert a suppressive capability. 25 Some evidence also shows that mast cells may be important mediators of Treg-dependent tolerance of allograft 26 Several tumor models have documented the accumulation of mast cells, as well as Treg cells at the tumor location.…”
Section: Immunologic Interaction Between Cancer and Aitmentioning
confidence: 99%